Communications, Signal Processing, and Systems The 2012 Proceedings of the International Conference on Communications, Signal Processing, and Systems - Liang, Qilian; Wang, Wei.; Mu, Jiasong; Liang, Jing.; Zhang, Baoju; Pi, Yiming; Zhao, Chenglin; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
Communications, Signal Processing, and Systems is a collection of contributions coming out of the International Conference on Communications, Signal Processing, and Systems (CSPS) held October 2012. This book provides the state-of-art developments of Communications, Signal Processing, and Systems, and their interactions in multidisciplinary fields, such as Smart Grid. The book also examines Radar Systems, Sensor Networks, Radar Signal Processing, Design and Implementation of Signal Processing Systems and Applications. Written by experts and students in the fields of Communications, Signal Processing, and Systems.
A Hierarchy System for Automatic Target Recognition in SAR Images -- Cao Building Extraction of SAR Images using Morphological Attribute Profiles -- Variational Segmentation of Polarimetric SAR Image By Using A Continous Potts Model and Automatic Initialization -- Mismatched Signal Jamming to Synthetic Aper-ture Radar -- A CGRT-CLEAN Method for Circular SAR Three Dimensional Imaging -- Outage Probability Analysis of HANs in Multiuser Downlink Scenario for Smart Grid Communications -- Bidirectional Energy Management for Plug-in Hybrid Electric Vehicles via Vehicle-to-Grid -- Intelligent Power Management System based Impedance Identification Technology for Safety of Power Utilization -- Providing Destination-Location Privacy in Wireless Sensor Network using Bubble Routing -- New Scalar Encoding Method to Accelerate Point Multiplication in Elliptic Curve Cryptography -- Model and Simulation of Data Aggregation Based on Voronoi Diagram in Hierarchical Sensor network -- Lightweight Security for WSN Based on Network Coding -- Improved Energy Detection Spectrum Sensing Method for OFDM-Based Cognitive Radio System -- Power Allocation in OFDM based Cognitive Radio System -- The Infrared Image Enhancement Approach Based On Directionlet Transform -- Particle filter track-before-detect implementation on GPU -- An Improved Monopulse Forward-looking Imaging Algorithm -- Compressed sensing based on the Contourlet transform for image processing -- Revealing Image Splicing Forgery using Local Binary Patterns of DCT Coefficients -- Sampling Synchronization for OFDM-based System with Unified Reference Clock -- A New low voltage low power consumption comparator for Successive Approximation Register ADCs -- Frequency Coding Array for Range-Angle Dependent Beamforming -- The Robust Sparse PCA for Data Reconstructive via Weighted Elastic Net -- Research on Theory of Alomost Perfect Binary-Third-Order Cyclic Autocorrelation Sequences -- A Strategy of Network Coding Against Nodes Conspiracy Attack -- A new modulation diversity technique of 60GHz Millimeter-wave System to reduce PAPR -- Artificial Reflector Based Efficient NLOS Tranmissions in 60GHz Millitermeter-wave Wireless Communication -- A Novel Frequency Drift Tracking Algorithm Based on Kalman Filter in 60GHz mm-Wave System -- An Efficient Hybrid Beamforming For Uplink Transmissions of 60GHz Millimeter-wave Communications -- A Novel Phase Noise Compensation Scheme for 60GHz OFDM system based on Quantum Genetic Algorithm -- Physical Layer Network Coding Based Two-Way Relay For 60GHz Millimeter-wave Wireless Personal Area Networks -- A Novel Scheme of Improving 60GHz Millimeter-wave System Performance in the Presence of Nonlinear Power Amplifier -- An Improved Dynamic Progrmming Based Track-before-Detect Approach for Dim Target Detection -- FOD Detection on Airport Runway with Clutter Map CFAR Plane Technique -- An approach to the modulation recognition of MIMO radar signals -- Experimental Study of through-wall Human Detection by UWB Radar with Hilbert Huang Transform -- A novel pulse compression method for weather radar -- A Method of Obstacle Identification Based on UWB and Selected Bispectra -- Nonlinear Estimation for Ultra-wideband Radar Based on Bayesian Particle Filtering Detector -- Some Recent Results on the Physical Layer Security of Frequency Hopping Systems -- An Improved Adaptive Filtering Algorithm for Non-Sparse Impulse Response -- 60GHz Ultra-wideband Channel Estimation Based on Cluster-Classification Compressed Sensing -- The study about a novel Beam-search strategy in 60GHz wireless communication environment -- Routing Selection Strategy Based on Link Failure in ZigBee Networks with Changing Mobility -- Detecting Community Structure of Complex Networks based on Network Potential -- DOA Estimation Algorithm Based on Compressed-Sensing -- Acoustic Source Localization Based on Microphone Array -- GTD-based Model of Terahertz Radar Scattering Center Distance Estimation Method -- An Kalman Filter-Based Method for BeiDou/GPS Integrated Navigation System -- A 2-dimensional Correlation Interferometer Algorithm Based on Dimension Separation -- Improved Positioning Algorithm Using the Linear Constraints of Scatterer in Two Base Station -- Parameter estimation of target with micro-motion based on terahertz radar -- Terahertz radar signal for heart and breath rate detection based on time-frequency analysis -- Throat Polyps Detection Based on Patient Voices.
Keywords: Engineering; Computer network architectures; Telecommunication; Engineering; Communications Engineering, Networks; Signal, Image and Speech Processing; Computer Systems Organization and Communication Networks